Strategic incentives for market share - Ritz, R (University of Oxford, 2005)
Market share objectives are prominent in many industries, especially where managers pay much attention to league table rankings. This paper explores the strategic rationale for giving managers incentives based on market share in an oligopoly competing in strategic substitutes. Moreover, the paper discusses evidence on executive compensation practice in the automotive and investment banking industries. As predicted by the theory, firms in both industries use explicit contractual incentives based on market share. The profitability squeeze in the US car industry due to aggressive buyer discount programs can thus be understood as a consequence of prevailing management incentives.